The Value of Hindu Ethics in Elementary Education as a Reinforcement of Religious Moderation - I Wayan Agus Gunada (International Conference on Elementary Education, 2023)
This article aims to illustrate the importance of the ethical value of Hinduism in elementary education students as a guide for building a harmonious life between religious people. Harmonious life is indeed hoping for the Indonesian nation, but the existence of radical understanding and acts of intolerance is undoubtedly a threat. Thus, the internalization of ethical values for students in elementary education, of course, is a strengthening of religious moderation. This conceptual article was studied using the literature review method by analyzing relevant literature on Hindu religious education and religious moderation in elementary education. Based on the study's results, Hindu ethical values are essential in building students' character. Ethics is a guide in strengthening the internalization of religious moderation because Hindu ethics aims to make individuals behave well and respect differences. This is an essential foundation for strengthening religious moderation. Hopefully, this study will become a reference for research or relevant studies for strengthening religious moderation in the elementary education process and other levels of education.